2000
DOI: 10.1097/00005537-200003000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Conservative Surgery in T3–T4 Pharyngolaryngeal Squamous Cell Carcinoma: An Alternative to Radiation Therapy and to Total Laryngectomy for Good Responders to Induction Chemotherapy

Abstract: Objective: To evaluate the possibility of preservation of the larynx after neoadjuvant chemotherapy by performing a conservative surgery instead of total laryngectomy initially planned, in patients with previously untreated laryngeal and piriform sinus squamous cell carcinoma (SCC). Study Design: Retrospective study. Methods: A total of 115 patients treated at Tenon Hospital with induction chemotherapy from 1985 to 1995, all with initial indication of radical surgery, were available for the study. The clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 14 publications
1
10
0
1
Order By: Relevance
“…Beauvillain et al 12 observed 5‐year overall survival and 5‐year local control rates of 19% and 39% after chemotherapy followed by definitive radiotherapy. In a group of 34 patients, Urba et al reported a 35% rate for 3‐year overall survival, 13 a result that is similar to the 32% rate for 3‐year overall survival reported by Lecanu et al 14 Organ preservation rates have been similarly discouraging 12–14 …”
Section: Discussionmentioning
confidence: 61%
“…Beauvillain et al 12 observed 5‐year overall survival and 5‐year local control rates of 19% and 39% after chemotherapy followed by definitive radiotherapy. In a group of 34 patients, Urba et al reported a 35% rate for 3‐year overall survival, 13 a result that is similar to the 32% rate for 3‐year overall survival reported by Lecanu et al 14 Organ preservation rates have been similarly discouraging 12–14 …”
Section: Discussionmentioning
confidence: 61%
“…Furthermore, one must note that our main results, namely, a 91.4% 5-year actuarial local control estimate and an 89.8% overall laryngeal preservation rate, compare favorably with the overall 64% laryngeal preservation rate reported when induction chemotherapy and radiotherapy were used 6 and the 84% overall laryngeal preservation rate recently reported when a concurrent chemotherapy and radiotherapy protocol was used 7 in patients with advanced-stage squamous cell carcinoma of the larynx. From this perspective and from the results achieved in the current series, it appears clear to us and others [22][23][24] that (1) the response to induction chemotherapy regimen should be used for modification of the therapeutic strategy for pharyngolaryngeal carcinomas and (2) SCPL should be now completely integrated in the organ preservation strategies used worldwide in patients with advanced endolaryngeal invasive squamous cell carcinoma classified as T3.…”
Section: Commentmentioning
confidence: 85%
“…Varying opinions exist in the literature regarding the optimal treatment of supraglottic carcinoma 4, 6, 7, 14, 16, 19–22, 24, 26, 27, 36, 39, 57–60. Because there are no randomized data comparing radiotherapy with conservation surgery for early, “favorable” tumors, it is necessary to examine nonrandomized data.…”
Section: Discussionmentioning
confidence: 99%